A comparative study of CBO and ECBO for optimal design of skeletal structures. (June 2015) - Kaveh, A.; Ilchi Ghazaan, M.
Highlights: The colliding bodies optimization (CBO), is employed for size optimization of skeletal structures. The enhanced colliding bodies optimization (ECBO) is applied to two truss and two frame structures. The capability of the CBO and ECBO are compared through four benchmark examples. Abstract: The recently developed method, colliding bodies optimization (CBO), is employed for size optimization of skeletal structures. The enhanced colliding bodies optimization (ECBO) that utilizes memory to save some historically best solution and uses a random procedure to avoid local optima is also applied to skeletal structures. The capability of the CBO and ECBO are compared through two trusses and two frames structures. The design constraints of steel frames are imposed according to the provisions of LRFD-AISC. The numerical results show the successful performance of the ECBO algorithm in comparison to the CBO, and some other well-known meta-heuristics in structural optimization.